Self-Disclosure Of Generation Z Heavy Social Media Users In Bali - Sari, Wulan Purnama; Paramita, Sinta; Irena, Lydia (KOMUNIKA, 2025)
The digital era keeps evolving, particularly in terms of communication technology and internet usage. It is predicted that around 80% of Indonesia's population will have social media accounts by 2026, with the majority of users being Generation Z. The close relationship between Generation Z. Social media has given rise to the term "heavy social media users," referring to individuals who engage with social media for more than four hours a day. This study analyzes self-disclosure among Generation Z heavy social media users in Bali. The research adopts a quantitative approach, using a survey method. The population of this study consists of Generation Z individuals who are heavy social media users and reside in Bali. Nonprobability sampling, specifically purposive sampling, was used with predefined criteria. The findings indicate that while Instagram is the most frequently used social media platform by Generation Z, this group tends to engage in self-disclosure more on Twitter and TikTok, with an average of 10-12 times per day. Generation Z users distinguish between positive and negative self-disclosure, where positive disclosures are made public and accessible to many. In contrast, negative disclosures remain private and hidden from the broader social media audience.